Economic shocks, social disorganization, social capital, evaluations of police efficacy, and perceptions of safety in small Iowa communities - Recker, Nicholas Lee (2005)
Two very important issues facing small Iowa communities are the changing composition of small town economies and fear of crime. This paper examines the relationship between sudden events that significantly impact the local economy (economic shocks) and perceptions of safety and evaluations of police efficacy within small Iowa communities. In order to evaluate this relationship, data was collected from over 600 local key informant interviews from across Iowa and compared to over 10,000 surveys from randomly selected participants in 99 small Iowa communities. This paper utilizes social capital theory and social disorganization theory and examines their relationship to perceptions of safety and evaluations of police efficacy. I conclude that trust offers the greatest explanation of variance in perceptions of safety and evaluations of police efficacy